Tradisi Rokat Pandhebeh Menjelang Pernikahan Perspektif Urf di Desa Randuagung - Illah, Miftah Khasful; Kalamiah, Moh. Jeweherul; Safithri, Awaliya (Mabahits : Jurnal Hukum Keluarga Islam, 2025)
ABSTRACT. The Rokat Pandhebeh tradition is one of the customary ceremonies of the Randuagung Village community, Sumberjambe District, Jember Regency, conducted prior to marriage. This tradition embodies the meaning of purifying the bride and groom both physically and spiritually from all elements believed to bring misfortune or negativity, with the hope that they may enter married life in a state of purity and receive blessings. This study aims to examine the implementation of the Rokat Pandhebeh tradition before marriage and to analyze it from the perspective of ‘Urf (custom) in Randuagung Village. The research employs a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation in Randuagung Village. The research findings show that the Rokat Pandhebeh tradition is carried out through several stages, namely the preparation of ritual materials, the recitation of prayers, the sprinkling of flower water as a symbol of purification, and the distribution of food alms to the community. This tradition holds both social and spiritual functions, such as strengthening kinship, maintaining harmony, and preserving local culture. Based on the perspective of ‘urf, the implementation of Rokat Pandhebeh is categorized as ‘urf shahih (valid custom) because it does not contradict Islamic law. Keywords: Rokat Pandhebeh, ‘Urf, Marriage. ABSTRAK. Tradisi Rokat Pandhebeh merupakan salah satu upacara adat masyarakat Desa Randuagung, Kecamatan Sumberjambe, Kabupaten Jember, yang dilaksanakan menjelang pernikahan. Tradisi ini mengandung makna pembersihan diri lahir dan batin calon pengantin dari segala unsur yang dianggap membawa keburukan atau kesialan, baik secara fisik maupun spiritual, dengan harapan dapat memasuki kehidupan rumah tangga dalam keadaan suci dan memperoleh keberkahan. Penelitian ini bertujuan untuk mengetahui pelaksanaan tradisi Rokat Pandhebeh menjelang pernikahan dan Tinjauan Urf terhadap tradisi Rokat Pandhebeh menjelang pernikahan di Desa Randuagung. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus. Data diperoleh melalui observasi, wawancara, dan dokumentasi di Desa Randuagung, Hasil penelitian menunjukkan bahwa tradisi Rokat Pandhebeh dilaksanakan melalui beberapa tahapan, yakni persiapan perlengkapan, pembacaan doa, siraman air kembang sebagai simbol penyucian, serta pembagian sedekah makanan kepada masyarakat. Tradisi ini memiliki fungsi sosial dan spiritual, yaitu mempererat kekerabatan, menjaga keharmonisan, dan melestarikan budaya lokal. Berdasarkan tinjauan ‘urf, pelaksanaan Rokat Pandhebeh termasuk kategori ‘urf shahih (adat yang sah) karena tidak bertentangan dengan syariat Islam. Kata kunci: Rokat Pandhebeh, Urf, Pernikahan.